The role of triptans in the management of migraine - Meiyanti, Meiyanti (Faculty of Medicine, Trisakti University, 2009)
Migraine is one of the most prevalent disorders seen in clinical practice today and also a major cause of disability in the workplace. The prevalence of migraine is highest during the years of peak productivity, ie, between the ages of 25 and 55 years. The triptans are a group of selective 5-hydroxtriptamine (HT)1 serotonin receptor agonists that activate the 5-HT1B/1D receptor and possibly also the 5-HT1A dan 5-HT1F receptors. To date 7 subclasses of serotonin receptors have been identified, namely subclasses 5-HT1 to 5-HT7. Triptan causes cranial vasoconstriction, inhibits peripheral trigeminal activity and the trigeminal afferents. With its triple action, triptans can control acute attacks of migraine. Triptan is contraindicated in patients with previous ischemic or coronary artery disease, cerebral or peripheral vascular disease and other cardiovascular disorders. Triptans should be given immediately after an acute attack of migraine. The triptans are useful in the management of an acute migraine, but are not indicated for preventive therapy of migraine. Several new advances in migraine management have been made in regard to the recognition of the disease, the pathogenesis of migraine, and the phenomenon of central sensitization. More treatment options become available to patients and prescribers, the impact of such therapy on worker productivity will become more important in determining the value of such interventions.